2002
DOI: 10.1038/sj.bjc.6600475
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis between chronic pancreatitis and pancreatic cancer: value of the detection of KRAS2 mutations in circulating DNA

Abstract: KRAS2 mutations in codon 12 have been detected in about 80% of pancreatic cancers. The aim of this study was to evaluate the value of KRAS2 mutations detection in circulating deoxyribo nucleic acid to differentiate pancreatic cancer from chronic pancreatitis. Circulating deoxyribo nucleic acid was isolated from serum in 47 patients with histologically proven pancreatic adenocarcinomas (26 males, median age 65 years) and 31 controls with chronic pancreatitis (26 males, median age 48 years). Mutations at codon 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
3
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(95 citation statements)
references
References 32 publications
3
81
3
3
Order By: Relevance
“…8 In addition, mutant KRAS2 has been detected in pancreatic and duodenal juice from patients with chronic pancreatitis. 11,14,15 This makes it difficult to believe that simple qualitative detection of mutant KRAS2 could be a reliable tool for early diagnosis of pancreatic cancer. However, during cancer progression, cancer cell proliferation and invasion as well as luminal necrosis could result in accumulation of cancer DNA in the pancreatic juice, which may significantly increase the amount of mutant KRAS2 present in the juice of patients with cancer relative to that in patients with pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In addition, mutant KRAS2 has been detected in pancreatic and duodenal juice from patients with chronic pancreatitis. 11,14,15 This makes it difficult to believe that simple qualitative detection of mutant KRAS2 could be a reliable tool for early diagnosis of pancreatic cancer. However, during cancer progression, cancer cell proliferation and invasion as well as luminal necrosis could result in accumulation of cancer DNA in the pancreatic juice, which may significantly increase the amount of mutant KRAS2 present in the juice of patients with cancer relative to that in patients with pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, small quantities of mutant KRAS2 can also be detected in pancreatic duct juice from patients with chronic pancreatitis or pancreatic intraepithelial neoplasias (PanINs), which are considered the commonest precursor lesions to invasive pancreatic ductal adenocarcinoma. 8,11,14,15 These studies have not clearly indicated that KRAS2 mutations detected in pancreatic juice are from PanINs. Therefore, while qualitative detection of mutant KRAS2 alone is not an accurate predictor of pancreatic cancer, quantitative assays for KRAS2 mutations in biological fluids might be able to distinguish between pancreatic cancer and other conditions.…”
Section: Research Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of K-ras mutations in circulating DNA has a low sensitivity, but specificity was about 90% for the diagnosis of pancreatic cancer. 17 DNA hypermethylation has been detected in the pancreatic juice of patients with pancreatic ductal adenocarcinoma. 18 However, to our knowledge, there are no published reports pertaining to the detection of aberrant methylation in the plasma DNA of pancreatic cancer patients.…”
mentioning
confidence: 99%
“…[26] Attempts have been made to improve the utility of CA19-9 in differentiating benign from malignant head masses by combining it with other serum markers. Maire et al [33] investigated the value of detecting KRAS2 mutations in circulating DNA for diagnosing malignancy in this setting. The authors concluded that the finding of a normal CA 19-9 level and absence of KRAS2 mutations makes the diagnosis of pancreatic cancer extremely unlikely.…”
Section: Detection Of Pancreatic Cancer In Chronic Pancreatitismentioning
confidence: 99%